DEVELOPMENT OF A FIRE DAMAGE INDEX FOR IMMOVABLE CULTURAL HERITAGE - Gerardo Salazar (2021)
Available fire risk assessment approaches are mostly developed for new buildings. These approaches encompass minimum provisions defined by standards that are valid in certain countries, and few of these methods were thought exclusively for assessing the fire safety of cultural heritage. Given the diversity and specificity of cultural heritage assets, simple approaches are thus required to analyse their fire safety and establish their risk mitigation needs. In this context, a simplified fire damage index dedicated to assessing the fire vulnerability of immovable cultural heritage assets is proposed. The proposed index is the result of a weighted multi parameter evaluation that can be correlated with the level of damage that the cultural heritage asset (including its contents) is expected to suffer under a fire. The proposed index involves twenty-one indicators divided into four categories and offers a flexible approach for universal applicability. The performance of the proposed approach is illustrated for two case studies in Portugal. The results highlight the advantages of having a simple methodology that can be used for the preliminary risk analysis of a large number of assets to identify those those requiring risk mitigation measures or detailed and resource-demanding analyses.